The Influence of Government Internal Control System and Good Governance on Fraud Prevention in Purbalingga Environmental Service - Devi Nur Rahmah; Rudi Handoyono; Musyafa Al Farizi (Politeknik Negeri Semarang, 2025)
This study aims to analyze the influence of the Government Internal Control System and General Principles of Good Governance on fraud prevention at the Environmental Service of Purbalingga Regency. Data were collected through interviews and questionnaires using a modified Likert scale. The research sample was selected using a purposive sampling technique, with a total of 74 employees who met the criteria of having a minimum education of high school and at least two years of work experience. Data analysis was carried out by validity testing, reliability testing, classical assumption testing, and hypothesis testing using SPSS 25 software. The results showed that Government Internal Control System and General Principles of Good Governance had an effect on fraud prevention at the Environmental Service of Purbalingga Regency